The factors associated with the extra time spent on childcare during the covid-19 pandemic - Matlhaku, Thebe (My University, 2022)
This research report analyses the extra childcare undertaken at the time of the hard COVID-19 lockdown in South Africa. It explores whether the suspension of domestic work services in South Africa was associated with extra time spent on childcare by men and women who confirmed living with children in Wave 1 of the NIDS CRAM. The paper also evaluates whether there are distinguishing individual and household characteristics (excluding domestic work) that are associated with increased time spent on children. The aftermath of lockdown restrictions in an attempt to promote social distancing saw the freezing of domestic work services, and the shutdown of schools and early childhood centres (ECD’s). This period was also associated with additional time spent on children by both men and women. However, due to pre-existing inequalities among men and women, women have always spent more time on unpaid work and childcare in the home. The COVID-19 pandemic exacerbated these inequalities seeing women spend more time on children relative to men. Whilst men have increased their relative hours spent on childcare, absolutely, women spent more time on childcare. This study considers whether these gender differences persist after taking into account gender differences in individual characteristics (including labour market status) and household characteristics (including the number of young children and the presence of pensioners in the household).
A Research Report submitted in partial fulfilment of the Degree of Master of Commerce (Applied Development Economics) in the School of Economics and Finance, University of the Witwatersrand, 2022